Studies on cracking issues of pulsed electrodeposited Nickel-Tungsten thin films - Zhu, Jianfeng. (2009)
Nickel-tungsten (Ni-W) film has wide applications either as surface protective coatings for tooling, storage media, and plastic mold or as a thin film structure member in microelectronic and MEMS devices.